Penerapan Media Kartu Kata Dalam Meningkatkan Ketrampilan Membaca Peserta Didik Kelas 2 Pada Mata Pelajaran Bahasa Indonesia - Pratama, Vegas Albar; Wardana, Ludfi Arya; Kasdriyanto, Didit Yulian; Sriwijayanti, Ribut Prastiwi (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Based on the researcher’s observations during an internship at SDN Malasan Wetan 1, Probolinggo Regency, many second-grade students were still unable to read fluently. This issue was due to the lack of teacher skills and innovation in teaching reading, as well as minimal parental involvement in developing students' reading skills. Additionally, teachers relied solely on textbooks provided by the school without utilizing supplementary learning media. This study aims to improve reading skills by implementing word card media in Indonesian language learning for second-grade students at SDN Malasan Wetan 1. Word card media consist of small cards containing words and pictures that serve as learning aids. Reading skills are measured based on three indicators: clarity, fluency, and pronunciation. This research follows a Classroom Action Research (CAR) methodology, focusing on the classroom learning process through two cycles. The CAR stages include planning, implementation, observation, and reflection. The study subjects were second-grade students, and data analysis employed both qualitative and quantitative descriptive techniques. Data collection methods included interviews, observations, tests, and documentation.The results showed that implementing word card media effectively improved students' reading skills. The average score increased from 60.59 with a 52.9% completion rate in cycle 1 to 79.41 with an 88.3% completion rate in cycle 2, indicating a 35.4% improvement. Therefore, word card media can enhance the reading skills of second-grade students at SDN Malasan Wetan 1.